2010
DOI: 10.1038/oby.2010.51
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone Reduces Weight Gain and Improves Metabolic Abnormalities Associated With Risperidone Treatment in Normal Men

Abstract: IntroductIonThe potential for serious medical problems resulting from the use of second-generation antipsychotic medications has received extensive attention in the scientific literature. The propensity to induce significant weight gain, increase the risk of metabolic problems, and increase the risk of diabetes mellitus and hyperglycemia was first described in the early 1990s, shortly after the medications were approved by the US Food and Drug Administration. The earliest research reports noted significant wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 44 publications
2
34
0
1
Order By: Relevance
“…Previously, it had been shown that mifepristone treatment reduced adipose tissue mass gain and body weight gain in rodent models of diet-induced obesity (3,28,56). In addition, 2-4 wk of mifepristone treatment reduced risperidone-and olanzapine-induced weight gain in healthy men (23,24). This suggests that GCs play a significant role in contributing to fat deposition and weight gain in these studies.…”
Section: Adiposity Rebound After Daily Exercise and Cr Is Stoppedmentioning
confidence: 58%
“…Previously, it had been shown that mifepristone treatment reduced adipose tissue mass gain and body weight gain in rodent models of diet-induced obesity (3,28,56). In addition, 2-4 wk of mifepristone treatment reduced risperidone-and olanzapine-induced weight gain in healthy men (23,24). This suggests that GCs play a significant role in contributing to fat deposition and weight gain in these studies.…”
Section: Adiposity Rebound After Daily Exercise and Cr Is Stoppedmentioning
confidence: 58%
“…Prolonged use is not recommended, however, after short-term administration beneficial effects have been seen. These include decreased triglycerides (91), changes in HDL metabolism (92), limitation of antipsychotic-induced weight gain (93,94) and reduced fasting glucose and enhanced insulin sensitivity (95,96). A detailed analysis of GR antagonism to modulate lipid homeostasis has not been undertaken, however, In patients with type 2 Diabetes Mellitus, GRantagonism combined with inhibition of cortisol synthesis had equally beneficial effects to lower glucose and improve insulin sensitivity in those patients with and without NAFLD (95).…”
Section: Clinical Studiesmentioning
confidence: 97%
“…In a proof-of-concept clinical trial, mifepristone prevented the weight gain observed during treatment with olanzapine in healthy Indian men (Gross et al, 2009). In a similar trial, mifepristone also prevented the weight gain seen with risperidone (Gross et al, 2010). One of the challenges of finding novel clinical approaches has been identifying a suitable preclinical model to test a broad range of pharmacotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant reductions in weight, body mass index (BMI), and waist circumference were observed over 14-day treatment in drug-naïve patients treated with mifepristone and olanzapine versus patients treated with olanzapine alone (Gross et al, 2009). When combined with risperidone for 28 days, patients treated with mifepristone experienced reduced weight gain compared with patients treated with risperidone alone (Gross et al, 2010). In addition, improvements were noted in the insulin tolerance test, plasma triglycerides, plasma insulin, and the homeostasis model assessment of insulin resistance (HOMA IR ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation